Giant Adrenal Myelolipoma in a Patient without Endocrine Disorder: A Case Report and a Review of the Literature - Yoshifumi Nakayama; Nobutaka Matayoshi; Masaki Akiyama; Yusuke Sawatsubashi; Jun Nagata; Masanori Hisaoka; Keiji Hirata (Case Reports in Surgery)
We herein present a surgically treated case of huge adrenal myelolipoma. A 62-year-old woman presented to our surgical outpatient clinic with a retroperitoneal tumor. A clinical examination revealed an elastic soft, smooth-surfaced, painless, child-head-sized tumor with poor mobility, which was located in the left upper abdomen. Computed tomography (CT) and magnetic resonance imaging (MRI) of the abdomen revealed an uneven tumor surrounding the stomach, spleen, pancreas, and left kidney, which was 20 × 18 × 10 cm in size. The retroperitoneal tumor was resected. The tumor was attached to the surrounding organs, including the pancreas, spleen, and left kidney, but had not directly invaded these organs. The tumor was yellow and elastic soft and covered with a thin film. The origin of the tumor was suggested to be the left adrenal gland. The weight of the excised tumor was 1500 g. The histopathological diagnosis was adrenal myelolipoma. The patient had an uneventful recovery and was discharged from the hospital on the thirteenth day after the operation. She has been followed up in our outpatient clinic.